PELATIHAN PEMBUATAN JAMU HERBAL SEBAGAI PENGGANTI SUSU UHT UNTUK LANSIA - M. Hilmy Hidayatullah; Mahruroh Mahruroh; Alfi Nur Qomariah; Sofia Kusnaedi (LP2M Universitas Ibrahimy, 2025)
As a tropical country, Indonesia has a lot of plants. Some of them are believed to be useful for herbal medicine to prevent or even cure many diseases. However, not many Indonesians know that the traditional herbal drink which is known with “jamu” can be a substitute of UHT milk for elderly people. The goals of the researchers were to improve health for the society, especially for elderly people. This study was done to overcome health problems in society, especially in Bondowoso. Herbal drink can be an excellent alternative for villagers because it is cheap, the materials are easy to find, easy to make, and for heritage sustainability. Besides, it was also hoped to improve the living standards of society by selling it in many platforms. ABCD (Asset-Based Community Development) Method was applied in this research. This was done in Pekauman Village, Grujugan District, Bondowoso Regency. The result showed that the training to make traditional herbal drinks was held successfully. Most of society could make the herbal drink well. This activity was useful for the Pekauman people because it could increase their immune system, and increase their living standards. The result of the training was hoped to keep going on continually after the training was done.